KONSEP KHILAFAH MENURUT AR-RANIRY DAN SYIAH KUALA: (Suatu Analisis Diskriptis) - Ahmad Syarbaini (AZKIA : Jurnal Aktualisasi Pendidikan Islam, 2022)
Islamization Aceh is done directly by the preacher (missionaries) of Islam of the Arab. Pengislaman Aceh by the Arab nations did not have implications on the cultural Arabization Aceh. Acehnese culture develops based on the jurisprudence of Aceh (local wisdom), especially in the 17th century AD It is identified based on the legal principle established by ar-Raniry and Syiah Kuala basic thinking about the legal permissibility of Acehnese women's role in public life. The legal principle is built on the concept of "caliphate". The principle of the law is not nurtured in Arabia at that time, even until now. Male superiority was evident in Arabic. Khazanah thought jurisprudence in Aceh in the 17th century AD should be reflected in the next century. But the jurisprudence of thought disappear with the death of Syiah Kuala. Ages 18 M. The superiority of men as well as in the Arab raised.